Techno-biblical translation and epistemological shift in African theological education (2025)
This study examines the enduring significance of Bible translation as both a historical phenomenon and a central component of biblical hermeneutics, highlighting its distinctive textual mandate and insightful cultural implications. While Africa played a pioneering role in early biblical translation, contemporary African theological education faces the challenge of optimally integrating modem technological tools to enhance interpretive depth and accessibility, often adhering to less dynamic traditional methods. It is against this backdrop that this research introduces techno-biblical translation as a procedure that systematically merges traditional scriptural understandings with digital innovations. Employing a descriptive approach and engaging specific Yoruba Bible translations, the study explores the theological and cultural implications of this connection. Findings reveal that integrating digital resources—including e-Bibles, translation software, and online linguistic tools—is imperative for fostering an epistemological shift thereby enabling more accurate exegesis, clarifying textual ambiguities, and significantly improving the efficiency and effectiveness of theological instruction and ministerial practice in the African context. Thus, African theological stakeholders are enjoined to embrace these theological advancements for richer engagements and enhanced Christian outreaches.